Low back pain: what should a doctor know? - N. V. Pizova (Медицинский совет, 2020)
Low back pain is an important public health problem and one of the major causes of disability worldwide, as well as a symptomatic and benign condition. The article describes the main mechanical, systemic and non-specific causes of pain development. The “red flag” symptoms, which call for special attention from the practitioner, are considered in detail and if they are detected, a thorough diagnostic search for the causes of the pain syndrome is required. It is noted that a specific cause of pain can only be detected in a small percentage of patients. Emphasis is placed on the diagnosis and differential diagnosis carried out in individuals with low back pain, indicating the features of anamnestic data and the results of an objective examination. Non-contrast magnetic resonance imaging is considered the best imaging method for examining low back pain, when conservative treatment fails or when red flag symptoms indicating the underlying cause of the pain are present. Imaging is not recommended for most patients with nonspecific mechanical low back pain. The author presents the main therapy approaches in the treatment of acute and chronic low back pain. Several treatment methods can be used to treat acute or chronic low back pain, which are aimed at reducing the intensity of pain syndrome and improving the patient’s quality of life. The main groups of drugs used in these patients are described. Non-steroidal anti-inflammatory drugs and nimesulide in particular are discussed in more depth.